2007
DOI: 10.1051/cocv:2007009
|View full text |Cite
|
Sign up to set email alerts
|

Uniform stabilization of a viscous numerical approximation for a locally damped wave equation

Abstract: Abstract. This work is devoted to the analysis of a viscous finite-difference space semi-discretization of a locally damped wave equation in a regular 2-D domain. The damping term is supported in a suitable subset of the domain, so that the energy of solutions of the damped continuous wave equation decays exponentially to zero as time goes to infinity. Using discrete multiplier techniques, we prove that adding a suitable vanishing numerical viscosity term leads to a uniform (with respect to the mesh size) expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
(46 reference statements)
0
39
0
Order By: Relevance
“…In (Münch and Pazoto, 2007), it is shown that this scheme is a convergent approximation of (1) under the condition Δt ≤ h/ √ 2 and provides a uniform approximation of the energy as h and Δt tend to zero. The same modification is needed for the adjoint problem.…”
Section: Solution Of the Wave Equations (1) And (14)-introduction Of mentioning
confidence: 99%
See 3 more Smart Citations
“…In (Münch and Pazoto, 2007), it is shown that this scheme is a convergent approximation of (1) under the condition Δt ≤ h/ √ 2 and provides a uniform approximation of the energy as h and Δt tend to zero. The same modification is needed for the adjoint problem.…”
Section: Solution Of the Wave Equations (1) And (14)-introduction Of mentioning
confidence: 99%
“…leading to a centered scheme of order two in space and time, which is stable under the condition Δt ≤ h/ √ 2 (we refer to (Münch and Pazoto, 2007) for details). However, as observed initially in (Banks et al, 1991) in the context of stabilization and in (Glowinski et al, 1989) in the context of exact controllability, this scheme is not uniformly convergent with respect to the dissipation property.…”
Section: Solution Of the Wave Equations (1) And (14)-introduction Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, damping is whether an unavoidable presence in physical reality or a desired characteristic in design. The use of advanced numerical techniques to solve the related PDEs, such as FEM and the finite difference methods (FDM) is well established and it is standard in this framework , even if the research of a numerical method that could reproduce the expected damping decay is an actual argument in literature (see [14][15][16] and their references). On the other hand, in the context of BEMs the analysis of dissipation through damped wave equation rewritten as a BIE is a relatively new topic, because it has been scarcely investigated until now.…”
Section: Introductionmentioning
confidence: 99%